Transformation of Salalahuk Tradition: A Media for Character Building and Strengthening the Value of Tauhid in Pesantren Education - Muhammad Fathurrozaq; Zainur Rofiq Hadiyatullah; Mohammad Asrori (Educazione: Journal of Education and Learning, 2025)
This research focuses on exploring the Salalahuk tradition as a medium for spiritual education and character building in Senden Village Islamic boarding school, Kampak, Trenggalek. This tradition is integrated in non-formal learning, especially during the month of Ramadan, by involving the chanting of tawhid-valued poems, joint reflection, and group discussion. The purpose of this study is to reveal how local traditions can be an effective pedagogical tool in supporting Islamic religious learning. This research uses a qualitative method with a descriptive-analytical approach. Data were collected through direct observation, in-depth interviews with pesantren caregivers, santri, and community leaders, and analysis of related documents. The results showed that Salalahuk effectively conveys the values of tawhid through the medium of local culture, creating a deep spiritual experience for the participants. This tradition is also proven to strengthen the character of santri by instilling moral values such as honesty, responsibility, and solidarity. In addition, Salalahuk creates a holistic educational approach that integrates formal and non-formal elements, thus strengthening not only the cognitive but also affective and social aspects of learners. The implications of this research show that local traditions can be adapted as a relevant and contextualized religious education model. This research makes a significant contribution in enriching the literature of local culture-based Islamic education. However, the limitations of this study include limited location coverage and qualitative-based methods. Further research is needed to expand the analysis in various locations and use quantitative approaches to get a more comprehensive.